The Theory of Mind Performance in School-Age children with Down syndrome and autism spectrum disorder - Nazila Shojaeian (Revista Discapacidad, Clínica, Neurociencias, 2022)
Theory of Mind (ToM) is ability in children and adolescents plays a key role to achieve the cognitive development, emotional and social cognition, which can enhance their communication ability. The study reported herein explored the comprehension of the ToM in Down syndrome (DS), Autism Spectrum Disorders (ASD), and typically development children (TD) during middle childhood and examined the role of IQ in the Theory of Mind. The participants were 74 Iranian school-aged between 6 and 12 years who participated in three groups: 24 ASD, 24 DS, and 26 TD. Children were compared to ToM tasks and first-, second-and third-order ToM tasks. Participants’ IQs were measured using the Raven’s Progressive Matrices (RPMs). We used SPSS 25 for analysis of variance (ANOVA), and correlation coefficient to assess the differences between the groups on ToM tasks. The level of significance was set at .05. These results show consistency with previous literature. TD group performed better than both clinical groups in all orders. ASD was competent to pass the first-order ToM tasks better than DS (p< .001). These findings suggest that second-order did not show statistically significant in clinical groups. It also finds statistically significant between the TD group than both other groups (F= 55.13, p< .001). For the third-order, children with DS did not perform statistically significant different (F= 4.99, p = 0.010) than children with ASD, and nor we found between ASD and TD groups. The IQ was significantly correlated with orders of false belief understanding. The significant consideration is required in further studies with more wide samples in other groups of neurodevelopment disorders.